2000
DOI: 10.1111/j.1748-0361.2000.tb00451.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality‐of‐Care Challenges for Rural Health

Abstract: The purpose of this article is to examine the issue of quality of care in rural America and to help others examine this issue in a way that is consistent with the very real challenges faced by rural communities in ensuring the availability of adequate health services. Rural citizens have a right to expect that their local health care meets certain basic standards. Unless rural providers can document that the quality of local health care meets objective external standards, third-party payers might refuse to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 11 publications
1
50
0
1
Order By: Relevance
“…Keeler and colleagues (46) drew strong responses from other researchers and rural health advocates when they found that rural and nonteaching hospitals have lower levels of quality (9). The rural research center at the University of Minnesota completed an overview of issues related to quality of care in rural versus other places in the United States (57). This review points to the few studies of quality that consider rural conditions and the realities of the workforce and practice conditions in rural communities.…”
Section: Quality Of Care In Rural Placesmentioning
confidence: 99%
See 1 more Smart Citation
“…Keeler and colleagues (46) drew strong responses from other researchers and rural health advocates when they found that rural and nonteaching hospitals have lower levels of quality (9). The rural research center at the University of Minnesota completed an overview of issues related to quality of care in rural versus other places in the United States (57). This review points to the few studies of quality that consider rural conditions and the realities of the workforce and practice conditions in rural communities.…”
Section: Quality Of Care In Rural Placesmentioning
confidence: 99%
“…However, developments in technology and organization, including the expansion of the use of telemedicine and an increase in the numbers of rural hospitals and rural practitioners becoming parts of alliances and systems, captured the attention of rural health services researchers as well as policy makers. As quality of care became an important issue and a larger proportion of the nation's population was covered by managed-care plans (34), rural providers were not left out of the trend toward greater scrutiny over practice decisions, especially when costs could be reduced (57). More attention is being ?…”
Section: Introductionmentioning
confidence: 99%
“…Quality of care has received the bulk of attention starting in 1999 [28] with a concern for the challenges of rural quality of care, appropriate assessment tools, and the need to clarify a primary quality-of-care objective [29] . It was argued that rural facilities should demonstrate an ability to provide care at a level of quality comparable to urban organizations.…”
Section: Qualitymentioning
confidence: 99%
“…It was argued that rural facilities should demonstrate an ability to provide care at a level of quality comparable to urban organizations. Since then, the research question has focused on how best to define, measure [29,30] , compare [31,32] , and report quality-of-care outcomes [14] in rural facilities, especially CAHs.…”
Section: Qualitymentioning
confidence: 99%
See 1 more Smart Citation